PATTERNS OF COMMUNICATION BETWEEN CHILDREN AND PARENTS (CASE STUDY OF BROKEN HOME FAMILIES IN PENGGALANGAN VILLAGE COMMUNITY, TEBING SYAHBANDAR DISTRICT) - Purnama Sari, Siti (CV. Radja Publika, 2022)
Indication representation is the transaction of communication delivery nailed into a single credible insigne that contains meaning, from missing stimuli to ever -changing individual behaviors. Included in the poor families for this generalization, the researcher wants to introduce the Pattern of Interpersonal Communication between Children and Parents (Case Study of Broken Home Family in Penggalangan Village Community of Tebing Syahbandar District). The euphemistic conception previously possessed in this reflection is the imperfect Theory of Interpersonal Relationship Predilection (FIRO). This conception is a previously possessed euphemistic for reflection on interpersonal needs and interpersonal processes that accommodate disclosure, trust, and empathy. The preliminary arrogance of this conception is that a characteristic is not intended to be told to others because it is supported by interpersonal needs. The evaluation of previously possessed euphemistic dispositions is qualitative descriptive. The previous euphemistic collection procedure was to arrange a press conference with the informants one by one. The consequences of this thinking suggest that interpersonal indications in Broken Home Families and proportionate relatives have first -class commitment. Meanwhile in poor households and relatives who do not conform to interpersonal indications with their offspring do not run favorably so that the exploitation of the heart and temperament of the offspring is not detected by his materfamilia like a flying crow raises the conscience. and the temperament of his offspring is incompatible with that of a conventional child sold freely. The recommendation of this evaluation is that under any circumstances and no complications whatsoever in a large conference family, they are required to be more appropriate in its continuation for their children, both acting and interacting directly. The consequences of this thinking suggest that interpersonal indications in Broken Homed Families and proportionate relatives have first -class commitments. Meanwhile in poor households and relatives who do not match the interpersonal indications with their offspring do not run favorably so that the exploitation of the heart and temperament of the offspring is not detected by his materfamilia like a flying crow raises the conscience. and the temperament of his offspring is incompatible with that of a conventional child sold freely.